2013
DOI: 10.1002/mrd.22230
|View full text |Cite
|
Sign up to set email alerts
|

Post‐hatching development of in vitro bovine embryos from day 7 to 14 in vivo versus in vitro

Abstract: This study evaluates the post-hatching development of in vitro-produced (IVP) embryos until Day 14. On Day 7, IVP embryos were either transferred to recipient uteruses or placed in a post-hatching development (PHD) system. As a control group, in vivo-produced (IVV), Day-7 embryos were also transferred to recipient uteruses. All groups were collected on Day 14 and were morphologically evaluated. Day-7 and Day-14 IVV and IVP embryos were used for quantification of eight genes (PLAC8, CD9, SLC2A1, SLC2A3, KRT8, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
8
25
0
Order By: Relevance
“…Nevertheless, there was a trend for the split embryos to be smaller than controls; elongated embryos derived from split blastocysts were in average smaller than 100-mm length. This is in agreement with others who also found variations in embryo size and recovery after distinct manipulation procedures [18,19,23,50,51] and with our own previous data [12] and those of Betsha et al, 2013 [50] on recovery and morphometry of cloned and IVP bovine embryos. Both groups confirmed that cloned elongated embryos were shorter than controls.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, there was a trend for the split embryos to be smaller than controls; elongated embryos derived from split blastocysts were in average smaller than 100-mm length. This is in agreement with others who also found variations in embryo size and recovery after distinct manipulation procedures [18,19,23,50,51] and with our own previous data [12] and those of Betsha et al, 2013 [50] on recovery and morphometry of cloned and IVP bovine embryos. Both groups confirmed that cloned elongated embryos were shorter than controls.…”
Section: Discussionsupporting
confidence: 94%
“…The bovine embryo in vivo develops further to the elongation stage where a new set of complex changes occur and the elongating conceptus gets in close communication with the uterine epithelium, to complete the implantation and the establishment of the pregnancy [18]. In this period also occurs the largest number of pregnancy losses, before the maternofetal recognition [2,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLAC8 expression has been reported in many species, such as zebrafish (3), mice (1), bovines (4)(5)(6)(7)(8)(9), and rabbits (16). However, little is known regarding PLAC8 expression in human oocytes and embryos.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that PLAC8 plays a crucial role in normal embryo development (3). In the evaluation of bovine embryo quality, PLAC8 is a biomarker that is used to predict pregnancy outcome (4)(5)(6)(7)(8)(9). Two recent reports investigated bovine embryos derived in vitro (4) and in vivo (10), and they demonstrated that PLAC8 was highly expressed in cells from embryos that were capable of developing into calves.…”
mentioning
confidence: 98%